Penerapan model pembelajaran realistic mathematical education(RME) untuk meningkatkan minat dan prestasi belajar matematika siswa kelas VIII MTs Negeri Prembun tahun pelajaran 2014/2015 - Hajar Kurniasih (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2015)
The aim of this research are to know (1) application of student learning Realistic Mathematical Education (RME) method (2) interest and achievement of mathematics study with student learning Realistic Mathematical Education (RME) and (3) the effectivity of student learning method Realistic Mathematical Education (RME) in increasing the interest and achievement of study the mathematics of student MTs Negeri Prembun grade VIII in Academic Year 2014/2015. The result of the research shows that the application of student learning Realistic Mathematical Education (RME) method can increase the interest and student’s result study on mathematics. The increasing of student’s interest in learning Mathematics can be seen from the increasing of all student’s interest score. The increase of 80% is fulfilled. The increasing of learning achievement was shown at pra cycles. There were 9 students who get mark more than passing grade (KKM), at first cyclus found 18 students (52,94%) who get mark more than passing grade (KKM), at second cyclus found 30 students (88,23%) who get mark more than passing grade (KKM).